Crafting Effective Marketing Strategies for Xiaomi in Indonesia Through SWOT Insights - Riu, Isma Azis (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to determine the marketing strategy undertaken by Xiaomi Indonesia and to describe effective suggestions based on the SWOT analysis conducted. The analysis was carried out using the IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) methods which describe the internal and external factors of a company which will then be followed up with an analysis diagram to determine the company's position. Xiaomi Indonesia occupies the WT quadrant position with scores (-0.9) and (-0.8) which indicate that an effective strategy that can be implemented is a defensive-aggressive strategy.